2022
DOI: 10.3390/jcm11092414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Women’s Age and Ultrasonographic Features to Choose Surgical Treatment for Endometriosis Associated with Ovarian Cancer

Abstract: Adequate surgical management of malignant endometriosis remains a clinical challenge in gynecology. Age, sonography variables, and tumor biomarkers have been reported as candidates in the clinical decision. This study aims were to analyze the factors of women’s age, body mass index, ultrasound features, and tumor biomarkers to predict endometriosis-associated ovarian cancer in a large series of endometriomas and to study the surgical treatment performed in this cohort. In this retrospective study, we reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
7
4
Order By: Relevance
“…Udomsinkul et al 18 uncovered that CA125 of more than 117.6 U/mL was a sensitive index for the diagnosis of EAOC. However, in another study, there was no significant difference in CA125 level between EAOC and OEM 19 . In our study, we found that CA125 levels of patients with EAOC were higher than levels of patients with OEM, but the statistical difference was not significant.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Udomsinkul et al 18 uncovered that CA125 of more than 117.6 U/mL was a sensitive index for the diagnosis of EAOC. However, in another study, there was no significant difference in CA125 level between EAOC and OEM 19 . In our study, we found that CA125 levels of patients with EAOC were higher than levels of patients with OEM, but the statistical difference was not significant.…”
Section: Discussioncontrasting
confidence: 83%
“…Kuo et al 20 found that the sensitivity and specificity of HE4 in diagnosing EAOC were 81.6% and 98.7%, respectively. Moreover, another small sample sized study revealed that HE4 was not significantly elevated in patients with EAOC when compared with OEM patients 19 . However, in our study, it was shown that using 140 pmol/L as the cut‐off value, the sensitivity and specificity of HE4 in the diagnosis of EAOC were 13.6% and 99.4%, respectively.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Human epididymis protein 4 (HE4) is a novel tumor biomarker approved for determining the likelihood that an ovarian mass is cancerous, with a sensitivity similar to that of CA-125 but with superior specificity [ 64 ]. In a recent small cohort of 76 women, 59 with endometrioma and 17 with EAOC, serum CA-125, and HE4 levels did not differ between the two groups [ 65 ].…”
Section: What Is the Strategy For The Clinical Diagnosis Of Eaoc In R...mentioning
confidence: 99%